Efektivitas Penerapan Coso Internal Control Framework dan Implikasinya Terhadap Deteksi Fraud pada Badan Usaha Milik Negara - Lovely Audrey; Jamaludin Iskak (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
State-Owned Enterprises (SOEs) play a strategic role in Indonesia’s economy; however, operational complexity and the large scale of managed assets increase the risk of fraud when internal controls are ineffective. This study aims to analyze the effectiveness of the COSO Internal Control Framework implementation and its implications for fraud detection in SOEs. The research employs a qualitative approach with a comparative case study design involving PT Bank Negara Indonesia (Persero) Tbk. and PT Waskita Karya (Persero) Tbk. Data were obtained through document analysis of annual reports, corporate governance reports, regulations, and supporting publications. The results indicate that BNI effectively implemented the five COSO components, enabling faster fraud detection and response. Conversely, weak COSO implementation at Waskita Karya resulted in prolonged fraud with significant financial impacts. The control environment, particularly tone at the top, was identified as the key factor determining the effectiveness of the internal control system. COSO implementation does not eliminate fraud entirely but enhances organizational capability to accelerate fraud detection and limit its consequences